Narrow Excitonic Lines in Core–Shell Nanorods With InGaN/GaN Quantum Wells Intersected by Basal Stacking Faults. Issue 6 (18th March 2019) - Evropeitsev, Evgeniy A.; Robin, Yoann; Shubina, Tatiana V.; Bae, Si‐Young; Nitta, Shugo; Kirilenko, Demid A.; Davydov, Valery Y.; Smirnov, Alexandr N.; Toropov, Alexey A.; Kushimoto, Maki; Ivanov, Sergey V.; Amano, Hiroshi
Abstract : Individual core–shell GaN nanorods (NRs) with InGaN quantum wells (QWs), lying in non‐polar, semi‐polar, and polar planes, are investigated by micro‐photoluminescence ( μ ‐PL) spectroscopy. Complementary transmission electron microscopy (TEM) studies reveal the presence of basal stacking faults (BSFs), which intersect the QWs. Narrow peaks of excitonic emission were detected at the NR tips, where the BSFs can both cross the semi‐polar QWs and penetrate through the thick polar well. In the NRs without the polar wells, the peaks appear in the blue spectral range only, while in the NRs with such wells, the peaks also appear in the green spectral range. Polarization resolved μ ‐PL measurements reveal the scattering of linear polarization degree among the narrow peaks, as well as among individual NRs, although the dominant polarization of the narrow lines was normal to the NR axis. In general, these findings are consistent with the origination of the narrow excitonic lines from the intersections of the BSFs with QWs of different types. Abstract : Individual core–shell GaN nanorods with InGaN quantum wells (QWs) are investigated by micro‐photoluminescence (μ‐PL) spectroscopy and transmission electron microscopy (TEM). Narrow PL peaks in the blue and green spectral regions are interpreted as exciton emission from the intersection of QWs with basal stacking faults.